The role of the enterprises in the national innovation in Australia - Anh, Duong Hong; Hoa, Trieu Bao (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
"The role of enterprises in national innovation in Australia" leads to a case study of Australia’s ambition and innovation environment and the problems they are facing. The article highlights the close relevance of different sectors such as investment, import and export, information technology, administrative law with the core of enterprises to the improvement and development of the innovation environment. At the same time, the article also outlines the challenges, deficiencies and issues that the Australian government needs to improve in order to achieve the ambition of innovation. The article is based on the research results from the project "Australia 2030: Prosperity through innovation" of the Innovation and Science Australian - ISA. Code: 18092001